PERAN KEPALA SEKOLAH MELALUI PENERAPAN SISTEM AMONG DALAM MENGEMBANGKAN PENDIDIKAN KARAKTER PESERTA DIDIK DI SDN 04 TEGALSARI KABUPATEN PEMALANG - Windriati; Hansen Lutfiartha; Soedjono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze the role of the school principal in developing students' character education through the implementation of the among system at SDN 04 Tegalsari. The among system, rooted in Ki Hadjar Dewantara's educational philosophy, emphasizes the asah, asih, and asuh approach in the educational process. The school principal plays a strategic role in creating a school environment that supports character development by providing exemplary behavior, motivation, and policies oriented toward instilling moral and social values in students. This research employs a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation. The findings indicate that the principal acts as a manager, leader, and motivator in the implementation of the among system. Strategies applied include teacher development, strengthening school culture, and fostering collaboration with parents and the community. The impact is evident in the improvement of students' discipline, responsibility, and empathy. In conclusion, the principal's role in implementing the among system at SDN 04 Tegalsari has proven highly effective in developing students' character education. The study recommends enhancing teacher training and increasing school community involvement to ensure the program's sustainability.